Menumbuhkan Kreativitas dan Kemandirian Ekonomi melalui Wirausaha Buket: Growing Creativity and Economic Independence through Bouquet Entrepreneurship - Nissa, Ita Chairun; Yuntawati, Yuntawati; Pujilestari, Pujilestari; Masjudin, Masjudin; Noviyanti, Putu Ledyari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This entrepreneurial activity is carried out in the form of training in making flower bouquets and assistance in efforts to maintain and develop the business being formed. This entrepreneurial activity was motivated by the condition of the productive age population in the city of Mataram, NTB, especially in Lendang Lekong village. The productive age population consists of teenagers who are members of youth organizations. The results of the activities carried out show an increase in entrepreneurial attitudes, knowledge and skills in making bouquets and running a bouquet business to gain economic income.